Efficient Organocatalytic Dehydrogenation of Ammonia Borane. Issue 4 (10th December 2019) - Hasenbeck, Max; Becker, Jonathan; Gellrich, Urs
Abstract: Dehydrogenation of ammonia borane by sterically encumbered pyridones as organocatalysts is reported. With 6‐ tert ‐butyl‐2‐thiopyridone as the catalyst, a turnover frequency (TOF) of 88 h −1 was achieved. Experimental mechanistic investigations, substantiated by DLPNO‐CCSD(T) computations, indicate a mechanistic scenario that commences with the protonation of a B−H bond by the mercaptopyridine form of the catalyst. The reactive intermediate formed by this initial protonation was observed by NMR spectroscopy and the molecular structure of a surrogate determined by SCXRD. An intramolecular proton transfer in this intermediate from the NH3 group to the pyridine ring with concomitant breaking of the S−B bond regenerates the thiopyridone and closes the catalytic cycle. This step can be described as an inorganic retro‐ene reaction. Abstract : H2 go : Efficient dehydrogenation of ammonia borane by the organic catalyst 6‐ tert ‐butyl‐2‐thiopyridone is described. Mechanistic investigations show that the reaction commences with dehydrogenative S−B coupling. An inorganic retro‐ene reaction closes the catalytic cycle and regenerates the catalyst.